2010
DOI: 10.4103/1463-1741.59995
|View full text |Cite
|
Sign up to set email alerts
|

The associations between noise sensitivity, reported physical and mental health, perceived environmental quality, and noise annoyance

Abstract: One hundred and ninety residents around Frankfurt Airport (46% female; 17-80 years) were interviewed concerning noise annoyance due to transportation noise (aircraft, road traffic), perceived mental and physical health, perceived environmental quality, and noise sensitivity. The aim of the analyses was to test whether noise sensitivity reflects partly general environmental sensitivity and is associated with an elevated susceptibility for the perception of mental and physical health. In this study, the reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(102 citation statements)
references
References 44 publications
6
87
0
3
Order By: Relevance
“…Annoyance and sleep disturbance mediated the effects of NS on health. Schreckenberg et al, [66] concluded that NS people were more critical of their environmental quality, in particular with regard to air traffic. This phenomenon was earlier referred to by Weinstein as "critical tendency."…”
Section: Mechanismsmentioning
confidence: 99%
“…Annoyance and sleep disturbance mediated the effects of NS on health. Schreckenberg et al, [66] concluded that NS people were more critical of their environmental quality, in particular with regard to air traffic. This phenomenon was earlier referred to by Weinstein as "critical tendency."…”
Section: Mechanismsmentioning
confidence: 99%
“…Geurs and Van Wee, 2004). Moreover they differ in the way they perceive nuisance; studies looking into the relation between noise exposure and noise annoyance often fail to find a one-toone relationship (Job, 1988;Schreckenberg et al, 2010;Zimmer and Ellermeier, 1999;Miedema and Vos, 1999). Because of this notion, studies often conclude that subjective evaluations have more explanatory power (e.g.…”
Section: Accessibility Nuisance and Residential Satisfactionmentioning
confidence: 99%
“…Page 9 Not everyone will be affected in the same way by noise. Schreckenberg et al (2010) investigated the impact of environmental noise upon individuals who were noise-sensitive compared to those who were not. Their study found that noise exposure did not necessarily determine mental health effects, but rather noise annoyance was a predictor; noise sensitivity was found to influence noise annoyance.…”
Section: Noise Stress and Health Care Systemsmentioning
confidence: 99%